Genocide: truth, memory, and representation - Hinton, Alexander Laban (The cultures and practice of violence series, 2009)
What is an anthropology of genocide? : reflections on field research with Maya survivors in Guatemala / Victoria Sanford -- Perverse outcomes : international monitoring and the perpetuation of violence in Sudan / Sharon E. Hutchinson -- Whose genocide? whose truth? representations of victim and perpetrator in Rwanda / Jennie E. Burnet -- A politics of silences : violence, memory, and treacherous speech in post-1965 Bali / Leslie Dwyer -- The limits of empathy : emotional anesthesia and the museum of corpses in post-Holocaust Germany / Uli Linke -- Forgotten Guatemala : genocide, truth, and denial in Guatemala's Oriente / Debra Rodman -- Addressing the legacies of mass violence and genocide in Indonesia and East Timor: Truth, memory, and corruption / Elizabeth Drexler -- Mediated hostility : media, affective citizenship, and genocide in northern Nigeria / Conerly Casey -- Cleansed of experience? : genocide, ethnic cleansing, and the challenges of anthropological representation / Pamela Ballinger -- Epilogue : the imagination of genocide / Antonius C.G.M. Robben